2020
DOI: 10.1016/j.puhe.2020.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Policy determinants of COVID-19 pandemic–induced fatality rates across nations

Abstract: Objectives Coronavirus disease 2019 (COVID-19) is the most devastating pandemic to affect humanity in a century. In this article, we assessed tests as a policy instrument and policy enactment to contain COVID-19 and potentially reduce mortalities. Study design A model was devised to estimate the factors that influenced the death rate across 121 nations and by income group. Results Nations with a higher proportion of people aged 65+ years had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…In the present study, it was observed that Argentina and Colombia have a CDR of 51.6 and 52.2 in people over 30 and under 100 years old, respectively. Results similar analyzing data from 121 countries, 46 high-income, 36 upper-middle-income and 39 low, they found that the CDR of high countries is 2.16 times higher compared to upper-middle-income countries (166 vs. 77) and 6.1 times higher than poor countries (166 vs. 27) were recently reported (6).…”
Section: Discussionsupporting
confidence: 58%
“…In the present study, it was observed that Argentina and Colombia have a CDR of 51.6 and 52.2 in people over 30 and under 100 years old, respectively. Results similar analyzing data from 121 countries, 46 high-income, 36 upper-middle-income and 39 low, they found that the CDR of high countries is 2.16 times higher compared to upper-middle-income countries (166 vs. 77) and 6.1 times higher than poor countries (166 vs. 27) were recently reported (6).…”
Section: Discussionsupporting
confidence: 58%
“…We included two observational 43 44 and thirteen modeling studies 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 .…”
Section: Findings Of Included Studies On Effectiveness (N=65)mentioning
confidence: 99%
“…Da Silva et al found that delaying policies for international travel restrictions led to a higher case fatality rate to similar degrees as public information campaigns and testing. 56 .…”
Section: Findings Of Included Studies On Effectiveness (N=65)mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study estimated the cost of a future major epidemic or pandemic, including the valuation of lives lost, at 720,000 deaths per year at an annual loss of US$0.5 trillion per year equivalent to a cost of 0.6% of global income per year [11]. In a cross-sectional study of 121 nations, evidence showed that a delay in policy enactment, such as international travel restrictions and testing policies, led to a higher fatality rate relative to not delaying such mandates [12].…”
Section: Discussionmentioning
confidence: 99%